A typological analysis of the inflorescences of the genus Nassauvia (Asteraceae) - Tortosa, Roberto Daniel (2004)
The inflorescences of the genus Nassauvia are analyzed following Troll's comparative-morphological approach. Eight types of synflorescences are recognized, each defined by a particular combination of six developmental processes: truncation, proliferation, shortening of internodes, homogenization of paraclades, suppression of paraclades and shortening of peduncles. Decomposing each inflorescence type into six characters, each referring to a hypothesized developmental process, makes the data suitable for cladistic analysis. The synflorescence patterns described in the present analysis mostly correlate with currently accepted infrageneric classifications; discrepancies are discussed. Inflorescences currently described as "pseudocephalia" are shown to be strongly condensed panicles or stachyoids of heads. Sister group inspection suggests the condensed panicle of heads to be the basal inflorescence condition within the genus Nassauvia.